(1/3x)-(1/4)(x-1)=4x

Simple and best practice solution for (1/3x)-(1/4)(x-1)=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1/3x)-(1/4)(x-1)=4x equation:



(1/3x)-(1/4)(x-1)=4x
We move all terms to the left:
(1/3x)-(1/4)(x-1)-(4x)=0
Domain of the equation: 3x)!=0
x!=0/1
x!=0
x∈R
Domain of the equation: 4)(x-1)!=0
x∈R
We add all the numbers together, and all the variables
(+1/3x)-(+1/4)(x-1)-4x=0
We add all the numbers together, and all the variables
-4x+(+1/3x)-(+1/4)(x-1)=0
We get rid of parentheses
-4x+1/3x-(+1/4)(x-1)=0
We multiply parentheses ..
-(+x^2+1/4*-1)-4x+1/3x=0
We calculate fractions
(-(+x^2+1*3x)/(-1)*3x+4*)-4x+()/(-1)*3x+4*)=0
We calculate terms in parentheses: +(-(+x^2+1*3x)/(-1)*3x+4*), so:
-(+x^2+1*3x)/(-1)*3x+4*
We add all the numbers together, and all the variables
-(+x^2+1*3x)/(-1)*3x
We multiply all the terms by the denominator
-(+x^2+1*3x)
We get rid of parentheses
-x^2-1*3x
We add all the numbers together, and all the variables
-1x^2-1*3x
Wy multiply elements
-1x^2-3x
Back to the equation:
+(-1x^2-3x)
We add all the numbers together, and all the variables
(-1x^2-3x)-4x+()/(-1)*3x=0
We get rid of parentheses
-1x^2-3x-4x+()/(-1)*3x=0
We multiply all the terms by the denominator
-1x^2*(-1)*3x-3x*(-1)*3x-4x*(-1)*3x+()=0
We add all the numbers together, and all the variables
-1x^2*(-1)*3x-3x*(-1)*3x-4x*(-1)*3x=0
We multiply parentheses
-1x^2*(-1)*3x+9x^2+12x^2=0
We add all the numbers together, and all the variables
21x^2-1x^2*(-1)*3x=0

See similar equations:

| 12(c-5)=11(c+5) | | 4+8x=12+4x-12 | | 17x+3+43=13x | | -8x-(3x+-6)=4-x | | 5(-x-3)=20 | | 0=x+3-6 | | 634=4×160+n | | −6x+8=−3x−10 | | x+(x-47)=180 | | 2-8(-6x-1)=298 | | 6+3m/9=4 | | 102=69-7x=3x | | 0.4x-2.5=1.3x4.7 | | −6x+8=−6x+8=  −3x−10 | | 18x-40=13x+57 | | 23=m+6 | | c=(5/9)*(*F-32) | | 9=-4w+6 | | 4x+7(x-3)=-5x+43 | | 2(9n-6)÷52=2(7n+8) | | 41.57=8g+3.57 | | 1-7m+8=-5 | | 3x+32+2x-7=180 | | 1=-7m+8=-5 | | K-(5-3k)=7k+4 | | 4x−8= 7x−2 | | 640+32(h-40)=1056 | | 4x−8=7x−27x | | -16=2(4x=8) | | 1/4x4=3 | | 2=6/e | | 1.41b-5.27=8.928 |

Equations solver categories